1991
DOI: 10.1002/nur.4770140108
|View full text |Cite
|
Sign up to set email alerts
|

Multiple drug regimens: Medication compliance among veterans 65 years and older

Abstract: In this study we attempted to develop a profile that could be used prospectively to identify veterans over 64 years of age who might be at risk for medication noncompliance. Male veterans (N = 249) having from one to seven oral daily prescribed medications were studied. Instruments administered to determine their relationship to compliance were the Paired-Associate Test, the Mini Mental State, the Multidimensional Health Locus of Control, and the Standard Depression Scale. Compliance was determined by a pill c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 24 publications
(16 reference statements)
0
28
1
Order By: Relevance
“…Several studies have examined the correlation between compliance and cognition. The results vary [15,[22][23][24], probably due to the use of different measures of cognition.…”
Section: Introductionmentioning
confidence: 84%
“…Several studies have examined the correlation between compliance and cognition. The results vary [15,[22][23][24], probably due to the use of different measures of cognition.…”
Section: Introductionmentioning
confidence: 84%
“…We found that cognitive impairment was one of the predictors for poor compliance. Some other studies failed to ®nd an association between cognitive impairment and noncompliance [9,28]. Elderly persons with cognitive impairment are conveniently excluded from most medication compliance research, perhaps because researchers are afraid that these subjects cannot give accurate information for research purposes.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple medication use was reported to increase the risk of adverse drug events and noncompliance [6,7]. Some studies have shown that the rate of medication compliance with long-term therapy was only 40±60% in elderly people [4,8,9]. Medication noncompliance among elderly persons may result in declining health, increased costs for health care, and increased preventable hospital admission [10] or emergency department visits [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…There is, however, considerable inconsistency in findings and a number of other investigators have demonstrated no differences based on race/ethnicity. 4,13,16,48 It is unclear why minorities might have lower adherence, but most have postulated that it is not race, but the interaction of race and income that is related to adherence. For example, Akincigil et al 95 studied long-term adherence to pharmacotherapy after acute myocardial infarction and reported the risk of discontinuation was highest among patients from low-income neighborhoods.…”
Section: Discussionmentioning
confidence: 99%